2012
DOI: 10.1097/mlr.0b013e318263134b
|View full text |Cite
|
Sign up to set email alerts
|

The Consumer Assessment of Healthcare Providers and Systems (CAHPS) Cultural Competence (CC) Item Set

Abstract: Background There is a need for reliable and valid measures of cultural competence from the patient’s perspective. Objective This paper evaluates the reliability and validity of the Consumer Assessments of Healthcare Providers and Systems (CAHPS®) Cultural Competence (CC) item set. Research Design Using 2008 survey data, we assessed the internal consistency of the CAHPS CC scales using Cronbach alphas, and examined the validity of the measures using exploratory and confirmatory factor analysis, multitrait s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 39 publications
1
36
1
2
Order By: Relevance
“…Other studies have shown that non-English-preferring Asians tend to exhibit even lower ERT than English-preferring Asians. 3,5,18 These findings, along with those from our study, suggest that direct case-mix adjustment for Asian race/ethnicity, or indirect adjustment such as Asian language spoken at home (recently adopted for HCAHPS) 43 or Asian survey language (as used for MA/PDP CAHPS), 25 may improve the measurement of the quality of care provided by physicians, medical groups, hospitals, and health plans. Such adjustments would have little effect for most providers, but would be likely to notably and correctly increase the scores of those with large proportions of Asian patients.…”
Section: Discussionmentioning
confidence: 66%
“…Other studies have shown that non-English-preferring Asians tend to exhibit even lower ERT than English-preferring Asians. 3,5,18 These findings, along with those from our study, suggest that direct case-mix adjustment for Asian race/ethnicity, or indirect adjustment such as Asian language spoken at home (recently adopted for HCAHPS) 43 or Asian survey language (as used for MA/PDP CAHPS), 25 may improve the measurement of the quality of care provided by physicians, medical groups, hospitals, and health plans. Such adjustments would have little effect for most providers, but would be likely to notably and correctly increase the scores of those with large proportions of Asian patients.…”
Section: Discussionmentioning
confidence: 66%
“…As Weech-Maldonado et al describe in a companion manuscript,(21) literature review and examination of cultural competence theory yielded 5 domains of cultural competence: 1) Patient-provider communication; 2) Respect for patient preferences/ shared decision-making; 3) Experiences leading to trust or distrust; 4) Experiences of discrimination; and 5) Language services. In order to develop the 26 survey items, Weech-Maldonado et al gleaned relevant items from the existing CAHPS survey, from other cultural competency instruments in the literature and public domain, and from a Federal Register call for measures.…”
Section: Methodsmentioning
confidence: 96%
“…(21) Given the high prevalence of uninsured and underinsured minority populations in the US, we evaluated its performance in an uninsured/underinsured sample of patients with type 2 diabetes. Provision of culturally competent care may be particularly important among patients with chronic diseases such as diabetes, where treatment requires patient engagement, competent self-management, and an ongoing relationship between patient and clinician.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the development of CAHPS—CC can be found elsewhere. (4) We present the three CAHPS-CC domains that were psychometrically sound among both English and Spanish speakers in our participant population. (2) These domains include Doctor Communication - Positive Behaviors (5 items), Doctor Communication - Health Promotion (4 items), and Trust (5 items).…”
Section: Methodsmentioning
confidence: 99%
“…Racial/ethnic minorities are less likely than Whites to report they trust the health care system. (4) The Trust domain includes items which ask patients to report the extent to which they feel they can tell their provider anything, trust their provider with their medical care, and feel their provider tells the truth about their health. It also asks patients how much their provider really cares about them as a person and their health.…”
Section: Introductionmentioning
confidence: 99%